Does Proficiency Level Affect Learners’ Lexical Access in L1 and L2? - Bashori, Muzakki (OKARA: Jurnal Bahasa dan Sastra, 2021)
Proficiency level is one important factor that contributes to learners’ language performance. Learners with higher proficiency levels tend to perform lexical access better and faster than those with lower proficiency. This study aims to investigate whether proficiency level affects lexical access in L1 and L2. The research involved seven Indonesian university students of master’s and doctoral degree programs at a university in the Netherlands who possess different proficiency levels. Two scrambled texts in the participants’ L1 and L2 were employed to test the participants. Meanwhile, the paired-samples t-test and correlation analysis were used to report the experiment. The results revealed an insignificant difference and a negative correlation between proficiency level and the number of errors and reading time. However, on average, the more proficient learners outperformed the less proficient, thus indicating that they may possess more complex lexical access in L1 and L2. Further studies are needed to provide other useful insights on this topic.